The goals of Polish Ecological Policy in the European Union including forest Management - Krajewska, Barbara (Studia Ecologiae et Bioethicae, 2006)
The article contains an analysis of the primary terms and notions such as politics. Ecological politics, ecology, forest management, and basic information concerning the ecological policy in Poland and in the European Union.